Respostas

  • PeH
  • Ambicioso
2013-07-29T18:43:23-03:00
\bullet \ \text{P.A.:} \ (-73, -67, -61, ...) \\\\ \circ a_1 = -73 \\ \circ r = 6, \text{pois} -67 - (-73) = 6 \\ \circ a_n > 0 \\ \circ a_n = a_1 + (n - 1) \cdot r \\\\ \text{Ent}\tilde{a}\text{o:} \\\\ a_1 + (n - 1) \cdot  6 > 0 \\ -73 + (n - 1) \cdot 6 > 0 \\ 6n - 6 - 73 > 0 \\ 6n - 79 > 0 \\ 6n > 79 \\ n > \text{13 (aproximadamente)}

Se n deve ser maior que 13, significa que o próximo número em ordem crescente de progressão aritmética é o de posição n = 14. Assim:

a_{14} = -73 + (14 - 1) \cdot 6 \\ a_{14} = -73 + 13 \cdot 6 \\ a_{14} = -73 + 78 \\\\ \boxed{a_{14} = 5}
2 3 2